The network of permanent GPS stations in Central Europe analysed for purpose of regional geodynamics and troposphere studies - HEFTY, Ján; IGONDOVÁ, Miroslava (Contributions to Geophysics and Geodesy, 2008)
The results from analysis of the four-year interval of GPS observations in the network of more than 30 permanent stations situated in Central Europe, Alpine-Adriatic region and Balkan Peninsula are presented. The time series of site coordinate variations and zenith total delays (ZTD) are the analysis products which characterize the behaviour of the individual network stations. The main features of both series are the long-term drift and seasonal variability at the millimetre level for local coordinates and at the level of 50 millimetres for the troposphere induced ZTD.